Timeline Alignment of Multiple TV Contents - Segundo, Ricardo Mendes Costa; Santos, Celso Alberto Saibel (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
The concept of Viewer usually specifies someone who watches, listens and receives information available on his TV. However, the addition of the ability to run applications and access the Internet into TVs changes this concept, since the content shown in TV receivers are no longer under the total control of the TV stations and a viewer can access and view on the screen of your TV (or on a second screen) extra contents related to the program that they are watching. In fact, each viewer decides how to integrate these multiple contents generating unique and individual experiences. However, as these experiences are based on the access to different content sources, it becomes necessary to synchronize this content locally on each user’s reception platform. This paper proposes a generic model to synchronize content from different sources with a TV show on each client, independently of middleware and platform used. The model foresees the generation of sync points from the (main) content of a program, which are sent to customers and used locally to synchronize the different extra content accessed by the viewer with the main content. A proof-of-concept application is presented to evaluate the model. In the application, different audio streams and text related to a TV show are aggregated, reaching a high accuracy when synchronized.